2022
DOI: 10.3390/polym14214582
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the In Vivo Biocompatibility of Molecularly Imprinted Polymer Nanoparticles

Abstract: Molecularly imprinted polymer nanoparticles (nanoMIPs) are high affinity synthetic receptors which show promise as imaging and therapeutic agents. Comprehensive analysis of the in vivo behaviour of nanoMIPs must be performed before they can be considered for clinical applications. This work reports the solid-phase synthesis of nanoMIPs and an investigation of their biodistribution, clearance and cytotoxicity in a rat model following both intravenous and oral administration. These nanoMIPs were found in each ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[90] (Open Access) (b). [92] 。因此, 上述挑战也是分子印迹人工抗体临床转化前必须要 解决的关键问题。 总之,分子印迹人工抗体作为天然抗体功能的 最有潜力替代物,其在生物医学领域的应用正在逐 步被开发完善。在不久的将来,一定能成为人类减 轻病痛、治疗疾病的有力选择。 参考文献 Natural antibodies play an important role in immunology and clinical medicine. However, the synthesis process of natural antibodies is complex and costly, in particular, their storage, transportation and use need strict conditions and timeliness to ensure their activity.…”
Section: 分子印迹人工抗体作为酶抑制的概念由 Hauptmentioning
confidence: 99%
“…[90] (Open Access) (b). [92] 。因此, 上述挑战也是分子印迹人工抗体临床转化前必须要 解决的关键问题。 总之,分子印迹人工抗体作为天然抗体功能的 最有潜力替代物,其在生物医学领域的应用正在逐 步被开发完善。在不久的将来,一定能成为人类减 轻病痛、治疗疾病的有力选择。 参考文献 Natural antibodies play an important role in immunology and clinical medicine. However, the synthesis process of natural antibodies is complex and costly, in particular, their storage, transportation and use need strict conditions and timeliness to ensure their activity.…”
Section: 分子印迹人工抗体作为酶抑制的概念由 Hauptmentioning
confidence: 99%
“…For the selective extraction of branched cyclodextrins, photo-irradiated MIPs were synthesized using azobenzene as a functional monomer [ 138 ], and the purity of cyclodextrin could reach 90.8% after going through MIPs. To reveal the risk of MIPs, the in vivo behavior of nano MIPs was investigated by Kassem and co-workers [ 139 ], and nano MIPs were found in each tissue type. The nano MIPs can be cleared via both feces and urine; the low cytotoxicity lays the foundation for in vivo application of nano MIPs.…”
Section: Application Progress Of Imprinted Polymersmentioning
confidence: 99%
“…Taking into consideration the importance of the build-up and accumulation of non-biodegradable plastic in the environment, to the point that microplastics have been found in a number of water bodies as well as glaciers and water organisms [ 78 , 79 ], it would be foolish to consider a large-scale introduction of MIP nanotechnology into the world without considering the potential environmental implications. Fortunately, a number of studies have currently reported the effects of MIP NPs in vivo [ 80 , 81 , 82 , 83 , 84 ], in certain cases assessing their biocompatibility in-depth and actually finding that in their native form, certain types of MIP NPs actually elicit an immune response in vivo [ 85 ]. Thus far, to the best of our knowledge, no studies have been carried out to assess the environmental impact both in the short term and long term of these nanomaterials in their current non-biodegradable fashion.…”
Section: Biocompatibility and Biodegradabilitymentioning
confidence: 99%
“…As discussed previously, many of them would not be degradable and, therefore, could exert an accumulation effect, especially if the popularity and diffusion of MIP NPs escalate for diagnostic and pharmaceutical applications [ 87 , 88 ]. A recent study by Piletsky et al actually highlighted that certain types of these nanomaterials might exhibit a significant immunogenic potential [ 85 ], and, therefore, their disposal should be performed according to specific and safe procedures. It would be interesting to ascertain whether these effects are also template dependent, but these types of investigations are still in their infancy to confirm this hypothesis.…”
Section: Waste Managementmentioning
confidence: 99%